Production of Rape (Brassica Napus L) Under Diaper Waste-Moisture Conservation Field Technology (Global Journal of Science Frontier Research, 2023)
The purpose of this study was to test the effectiveness of growing vegetables under diaper waste moisture conservation technology and to incentivise diaper waste management in a way which reduces its ecological footprint through water and plant nutrients harvesting and conservation in agriculture Due to poor refuse collection in Chitungwiza which has encouraged improper disposal of diaper waste people resorted to the dumping of used disposable diapers at various dumping sites that have sprouted in most residential areas in the urban areas of Zimbabwe Diaper wastes currently not properly managed in a manner which adds value to the food chain while they contain significant amounts of nutrients coupled with their water holding capacity which is not being utilised to address challenges induced by climate change in the agricultural sector pertaining food security and climate resilience in urban agriculture hence the need to undertake this study An experiment to compare growth of vegetables under diaper waste treatment and a control without diapers was conducted Vegetable growth rate and soil moisture loss were monitored over 10 weeks